1979
DOI: 10.1128/aac.15.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon Sources on Antibiotic Resistance in Pseudomonas aeruginosa

Abstract: The metabolism of branched-chain amino acids, branched-chain acyl derivatives, D-glucose, L-glutamate, and Mueller-Hinton medium was investigated to determine their effects on the growth, lipid composition, and antibiotic susceptibility of Pseudomonas aeruginosa. The unsaturated fatty acid content of the readily extractable lipids was altered by growth on selected branched-chain amino acids and their acyl derivatives. Bacteria grown on branched-chain acyl derivatives became more susceptible to polymyxin B and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 15 publications
1
19
1
Order By: Relevance
“…Alteration of outer membrane permeability leading to drug resistance has sometimes been associated with modification of phospholipid composition, in particular for antibiotics interacting with components of the outer membrane, such as polymyxin B and aminoglycosides (7,8). No such changes were identified in this study (Fig.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…Alteration of outer membrane permeability leading to drug resistance has sometimes been associated with modification of phospholipid composition, in particular for antibiotics interacting with components of the outer membrane, such as polymyxin B and aminoglycosides (7,8). No such changes were identified in this study (Fig.…”
Section: Discussioncontrasting
confidence: 39%
“…Bacterial cells were grown in nutrient broth to early stationary phase, harvested by centrifugation, washed twice with saline, suspended in water, and freezedried. The readily extractable lipid fraction was obtained by chloroform-methanol (2:1) extraction by the method of Folch et al (11), as modified by Conrad et al (8). The phosphate content of the readily extractable lipid fraction was determined by the method of Ames and Dubin (1).…”
Section: Methodsmentioning
confidence: 99%
“…Each nutrient is often consumed through a dedicated utilization pathway that imports the nutrient into the cytoplasm and then shunts the nutrient into cellular metabolism. Utilization pathways in bacteria have been extensively studied for over 60 years to understand the molecular basis of gene regulation (1), although nutrient utilization has received renewed interest because of its impact on how probiotics and pathogens colonize the human gut, how antibiotic resistance genes are spread through horizontal gene transfer, and how these properties can be used in engineering microbial chemical factories (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…We planned the present study to create modifications in the cell surface of E. coli by using various growth media to investigate the role of yet uncharacterized components in ceftazidime susceptibility. This work was based on a previous study that showed that bacterial growth in various media results in changes in lipid composition (7) and that studies with bacteria with mutations that affect the structure of the LPS-phospholipid bilayer showed changes in bacterial susceptibility to hydrophobic or membrane-interacting antibiotics (20). The hope was to change E. coli surface properties (hydrophobicity and phospholipid content) to investigate a possible nonspecific lipophilic diffusion pathway for ceftazidime.…”
Section: Discussionmentioning
confidence: 99%